2018
DOI: 10.1101/438671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ceftolozane-tazobactam pharmacokinetics during extracorporeal membrane oxygenation in a lung transplant recipient

Abstract: 22Ceftolozane-tazobactam pharmacokinetics during extracorporeal membrane oxygenation (ECMO) 23 has not been previously studied. In this work we report on the ceftolozane and tazobactam 24 plasmatic levels in a lung transplant recipient during ECMO, treated with ceftolozane-tazobactam 25 (2g/1g, intravenously every 8 h, 1 h infusion) for a Pseudomonas aeruginosa pulmonary infection. 26Ceftolozane Cmax and Cmin, monitored during 96 hrs, remained above 60 and 20 µg/mL, 27 respectively, with optimal drug exposu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…44 Twelve studies reported 74 patients that were immunocompromised. 17,20,[25][26][27][28][29]39,40,42,43,45 Of these studies, two included only immunocompromised patients. 28,43 As with ICU patients, this is likely an underestimation as most multi-infection studies did not provide a breakdown by infection type.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…44 Twelve studies reported 74 patients that were immunocompromised. 17,20,[25][26][27][28][29]39,40,42,43,45 Of these studies, two included only immunocompromised patients. 28,43 As with ICU patients, this is likely an underestimation as most multi-infection studies did not provide a breakdown by infection type.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirty-two studies, comprising 650 patients (98.8% of patients), reported a causative pathogen. [15][16][17][18]47 The most prevalent causative pathogen reported was P. aeruginosa (92.8%; N = 603 patients; 31 studies), of which 11.9% (N = 72) were caused by non-resistant P. aeruginosa, or the resistance level was not speci ed, 0.5% (N = 3) were caused by carbapenemresistant (CR) P. aeruginosa, 73.3% (N = 442) were caused by MDR P. aeruginosa, 13.8% (N = 83) were caused by extensivelydrug-resistant (XDR) P. aeruginosa, and 0.5% (N = 3) were caused by pandrug-resistant (PDR) P. aeruginosa. In the other study that reported a causative pathogen, all patients (N = 47) had an extended-spectrum β-lactamase (ESBL)-positive Enterobacterales infection.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), (21, 22, 24, 27-29, 33, 34, 39-41, 43-45, 50, 51, 54, 56, 57, 59, 61, 62, 68-71, 73-77, 79-85, 87-92, 94, 95, 97-100) Spain (N = 15), (26, 28, 30-32, 35-37, 42, 47, 49, 58, 66, 79, 96) and Italy (N = 13). (18,20,23,25,48,52,53,55,64,67,72,79,86) A variety of study designs were captured: 27 were non-comparative retrospective studies, (18,19,22,24,25,28,32,33,40,41,79,81,(84)(85)(86)(87)(88)(89)(90)(91)(92)(94)(95)(96)(97)(98)(99) 14 were case series, (20, 21, 29, 31, 34-39, 42, 43, 82, 100) ve were comparative (including two cohort studies, (80,83) and three case-control studies, (23,…”
Section: Study Characteristicsmentioning
confidence: 99%